Indication for Antibiotic Prescription Among Children Attending Primary Healthcare Services in Rural Burkina Faso. (21st May 2021) - Sié, Ali; Ouattara, Mamadou; Bountogo, Mamadou; Dah, Clarisse; Compaoré, Guillaume; Boudo, Valentin; Lebas, Elodie; Brogdon, Jessica; Nyatigo, Fanice; Arnold, Benjamin F; Lietman, Thomas M; Oldenburg, Catherine E
Abstract: Of 61 355 visits by children <5 years old to 48 government-run primary healthcare facilities in Nouna District, Burkina Faso, 30 975 had an antibiotic prescribed (58% for pneumonia diagnoses). A minority of prescriptions were for diagnoses not requiring antibiotics, including malaria, nonbloody diarrhea, and cough without pneumonia.